Windows server 2008 Hyper-V : insider's guide to Microsoft's Hypervisor. - Kelbley, John, ....-; Sterling, Mike, ....-; Stewart, Allen, ....- (Indianapolis : Wiley, 2009)
Hyper-V is one of the top virtualization products, and this practical guide focuses on the essentials of Windows Server 2008 Hyper-V. Written by the Microsoft team behind the Hyper-V product, this book shows you how to perform key virtualization scenarios, such as server consolidation, software test and development, and a dynamic data center and demonstrates how Hyper-V can be used to reduce cost and eliminate the complexity of a server infrastructure by consolidating workloads to a small number of machines. In addition, the material addresses using DPM, and SCOM with VMM in order to maintain and manage Hyper-V environments.